Pengaruh Musik Kematian dalam Budaya Masyarakat Batak Karo Terhadap Penguatan Literasi Budaya Mahasiswa PGSD - Ginting, Bijak; Sidebang, Restio (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2025)
This study aims to analyze the effect of death music in Batak Karo culture on strengthening cultural literacy among students of the Primary School Teacher Education (PGSD) program. Batak Karo death music is an integral part of traditional funeral rituals that embody social, symbolic, and cosmological values, making it a potential learning resource based on local wisdom. This research employed a quantitative approach using a pretest–posttest design, complemented by qualitative data as reinforcement (mixed methods). The research subjects consisted of 32 PGSD students who participated in Art Education learning based on the study of Batak Karo death music. Data were collected through a cultural literacy questionnaire, observation, and documentation. Data analysis was conducted using descriptive statistics and gain score analysis. The results showed an increase in students’ cultural literacy scores from a mean pretest score of 64.20 to a posttest mean score of 81.45. The gain score of 0.48 indicated a moderate level of improvement. The highest improvement was found in indicators of cultural identity understanding and appreciative attitudes toward local traditions, while the indicator of multicultural awareness showed a stable increase. These findings indicate that learning based on Batak Karo death music has a positive effect on strengthening the cultural literacy of PGSD students. This study contributes to the development of culture-based learning and supports cultural preservation through formal education in primary teacher education programs.